Mainstreaming displacement in development policies: An analysis of Solomon Islands and Vanuatu approaches. Issue 1 (28th October 2022) - Endacott, Joanna; Alam, Shawkat
Abstract: Pacific Small Island Developing States are uniquely vulnerable to climate disasters due to their geography and capacity to address disaster, displacement and development challenges. Climate disasters often trigger internal displacement. Long‐term recovery responses are ad hoc and unsustainable, often resulting in protracted displacement that undermines development progress. As displacement poses cross‐sectoral challenges, a development policy approach encourages integrated, durable solutions for internally displaced persons and host communities. This article advocates for mainstreaming displacement into development policy rather than treating it as a distinct policy issue. The article outlines the role of international law in guiding national displacement practices and analyse the policy experiences of Vanuatu and the Solomon Islands. Vanuatu has experienced widespread disaster displacement events, and the Solomon Islands have seen communities permanently relocate due to climate change. The article examines governance and institutional barriers inhibiting effective policy design and implementation. It concludes that mainstreaming displacement into development policies will promote integrated, inclusive and sustainable solutions for protracted displacement.